2000
DOI: 10.1021/la990852g
|View full text |Cite
|
Sign up to set email alerts
|

Ion Transport in Micelle-like Films:  Soft-Landed Ion Studies

Abstract: Ion-transport processes across epitaxially grown micelle-like films in the form of liquid hydrocarbon/ water/hydrocarbon sandwiches were studied by a novel ion soft-landing technique. Centered inside of vapor-deposited glassy films of 3-methylpentane (166 monolayers) and methylcyclohexane (50 monolayers) was a water layer from 0 to 10 monolayers thick. From 90 to 150 K we time-resolved hydronium ion motion and found that the ions (D3O + ) clearly paused in the aqueous phase, being transiently trapped by solvat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…Precisely controlled tailoring of interfaces through soft landing of hydronium ions enabled a series of elegant studies of ion solvation at liquid interfaces as well as ion diffusion through liquid films deposited onto cryogenically cooled metal surfaces in UHV (Biesecker et al, ; Tsekouras et al, ; Wu et al, , ). These investigations demonstrated the unique advantages that ion soft‐landing brings to studying ion transport through aqueous (Wu et al, ) and organic (Tsekouras et al, ; Wu et al, ) films in addition to probing the properties of aqueous‐organic interfaces (Wu et al, ). Using this approach, it has been demonstrated that the viscosity of thin organic films decreases near the liquid‐vacuum interface resulting in enhanced ion mobility in the top monolayers of the film (Bell et al, ).…”
Section: Preparative Mass Spectrometrymentioning
confidence: 99%
“…Precisely controlled tailoring of interfaces through soft landing of hydronium ions enabled a series of elegant studies of ion solvation at liquid interfaces as well as ion diffusion through liquid films deposited onto cryogenically cooled metal surfaces in UHV (Biesecker et al, ; Tsekouras et al, ; Wu et al, , ). These investigations demonstrated the unique advantages that ion soft‐landing brings to studying ion transport through aqueous (Wu et al, ) and organic (Tsekouras et al, ; Wu et al, ) films in addition to probing the properties of aqueous‐organic interfaces (Wu et al, ). Using this approach, it has been demonstrated that the viscosity of thin organic films decreases near the liquid‐vacuum interface resulting in enhanced ion mobility in the top monolayers of the film (Bell et al, ).…”
Section: Preparative Mass Spectrometrymentioning
confidence: 99%
“…constant compared to the water molecules (16). Region III shows a condition when the formations of admicelle and micelle conformations are started at the surface.…”
Section: Resultsmentioning
confidence: 99%
“…We have studied some aspects of bulk hydronium diffusion in water ice [13], and found that hydroniums could move a few ML, up to about 10 ML [15], below 150 K, in ice films. But they could not move 15 ML below 150 K, and even by 190 K, could not move a substantial portion (<10%) of the way across 150-3000 ML ice films [13].…”
Section: Discussionmentioning
confidence: 99%